Retention of CAD-CAM Implant-Supported Ceramic Restorations Luted to Titanium Bases: A Systematic Review of in-vitro Studies - Shadid RM (Clinical, Cosmetic and Investigational Dentistry)
Rola Muhammed Shadid1,2 1American Board of Oral Implantology, Faculty of Dentistry, Arab American University, Jenin, Palestine; 2Private Practice, Tulkarm, PalestineCorrespondence: Rola Muhammed Shadid, Department of Prosthodontics, Faculty of Dentistry, Arab American University, P.O Box 240, Jenin, Palestine, Tel +970594494066, Email rola.shadid@aaup.eduAbstract: This review aimed to compare the results of laboratory studies performed on adhesion methods of CAD-CAM implant-supported ceramic restorations to titanium-bases to analyze the factors that could affect this bond strength. The review was directed according to the guidelines delineated in the Preferred Reporting Items for Systematic Review and Meta-Analysis statement. Three databases including PubMed, Google Scholar, and Cochrane were investigated to identify related in vitro studies that mimicked clinical settings and published in international peer-reviewed journals between January 2000 and September 2024. The search yielded 5191 records; of these, 51 full-text articles were evaluated based on eligibility criteria. Ultimately, 31 studies were included. Different factors were assessed as possible influencers on ceramic/Ti-base bonding stability and strength. These include Ti-base height, different mechanical and chemical surface pretreatments of bonding surfaces, ceramic restoration material, luting system, and others. Ti-base abutment height is an important factor and thus it is recommended to use adequate Ti-base abutment height, whereas 3-mm-height should be used cautiously in posterior region. Combination of mechanical and chemical pretreatments of both bonding surfaces seems to enhance the bond strength; however, smooth Ti-bases rather than micro-grooved ones most likely benefit from sandblasting pretreatment. While the type of resin bonding system may affect the bonding performance, the interaction of some cements with definite ceramic materials could enhance the bond strength. The clinician must consider all those factors to have an effective bonding.Keywords: dental implant, bond strength, Ti-base, ceramic restoration, resin cement, zirconia